Energy expenditure in relation to activity of lesser mouse deer (Tragulus javanicus) - ., Darlis; Abdullah, N.; Liang, J.B; Purwanto, B. (Elsevier, 2001)
Heat production (HP) of male and female mouse deer during eating, standing and sitting was determined using the open circuit respiration chamber (RC). The time taken for similar activities was also determined in an outdoor enclosure (OD). The animals were fed kangkong (Ipomoea aquatica), sweet potato (Ipomoea batatas) and rabbit pellet ad libitum. Male mouse deer consumed more dry matter (DM), organic matter (OM) and gross energy (GE) than female. The time for each activity of male and female mouse deer kept in RC and OD was similar. The average time spent in RC and OD for both male and female, respectively, for sitting (956 and 896 min/day) was significantly (P < 0.01) longer than standing (463 and 520 min/day) and eating (21 and 24 min/day). Heat production for male and female mouse deer, respectively, during eating was the highest (0.44 and 0.43 kJ/kg W0.75/min) followed by standing (0.37 and 0.33 kJ/kgW0.75/min) and sitting (0.26 and 0.26 kJ/kg W0.75/min). The difference in HP per min during standing between male and female was significant (P < 0.05). The HP for 08.00-14.00 h and 14.00-20.00 h periods were higher than 20.00-02.00 h and 02.00-08.00 h periods. The overall HP for males during 08.00-14.00 h and 14.00-20.00 h periods were significantly (P < 0.05) higher (114.8 and 119.2 kJ/kg W0.75) than female (107.5 and 110.4 kJ/kg W0.75), respectively. © 2001 Elsevier Science Inc.